(untitled) (Research, Society and Development, 2021)
Lettuce is a vegetable that can be produced in different cultivation systems, such as aquaponics. The objective of this work was to evaluate the performance of lettuce cultivars from the purple, american, smooth and curly lettuce groups in aquaponics. The system consisted of an area of approximately 10 m3, consisting of a 1 m3 fish breeding tank, a 240 L settling filter, a 240 L biological filter and nine 3 m long PVC channels. The experiment consisted of four treatments, which consisted of four groups of lettuce cultivars: purple (Carmine); American (Butter); lisa (Elisa) and; curly (Grand Rapids). The variables analyzed were fresh mass, length of root and stem and number of leaves. At 20 days, the highest fresh mass was found in the crisp cultivar (121.22g). For root length, the curly and American cultivars showed higher averages with 16.22 cm. Stem length was greater in smooth (11.88 cm) and curly (12.77 cm) cultivars. With 19.33 leaves, the largest number was found in the smooth cultivar. At 40 days, the cultivar Americana presented higher fresh mass (321.33g) and root length (20.55cm). As for the length of the stem, the curly cultivar presented the highest value (17.88 cm). For the number of leaves, cultivars americana (34.22), purple (33) and smooth (32.22) showed higher values. Therefore, in aquaponics there is a significant difference between lettuce cultivars from the purple, american, smooth and curly groups.